Forsaken but for gold: an economic study of slavery and mining in the colombian Choco, 1680-1810 (2022)
eng: On an October morning in 1963 this author arrived in Quibdó, Chocó, with seven other Peace Corps Volunteers. The tugged old D-C 3 we had flown circled for half-an- hour before breaking through the solid cloud cover to land on the gravel runway which served as Quibdo's airstrip. Within a few minutes we stepped out into one of nature's sauna baths and experienced several of the dominent physical features of the central Chocó— heat* humidity, and an almost constant cloud cover. Late in the afternoon the rains descended and continued throughout the night. Rain, heat, and humidity were constant companions for this volunteer while he lived and worked with the people of the Chocó town of Tado duting the next twenty-one months.